Physical House Sanitation and the Acute Respiratory Infections (ARI) in Children - Sri Handayani; Sarinah Basri K. (Universitas Muhammadiyah Palu, 2023)
The sanitation conditions of residential houses in the Indramayu Regency are mostly categorized as low, which can potentially trigger Acute Respiratory Infections (ARI). This research aims to determine the relationship between the physical sanitation of homes and ARI in toddlers within the working area of the Cantigi Community Health Center in the Indramayu Regency. The research method employed a cross-sectional approach, with a sample taken from a total population of 95 houses in the Cantigi Community Health Center area. Data collection methods included semi-structured interviews, observations, and measurements covering ventilation, natural lighting, humidity, and flooring. Statistical tests were conducted using ordinal scale data, and the Chi-Square statistical test was chosen due to its suitability for the data used. The confidence level was set at 95% with a significance level of 5%. To determine the strength of the relationship between independent and dependent variables, the contingency coefficient (CC) was used, scored from 0 (lowest) to 1 (highest), and data processing was performed using SPSS version 24. Based on the research results, the Chi-Square test yielded the following values: ventilation p = 0.000 and CC = 0.455, lighting p = 0.000 and CC = 0.358, humidity p = 0.000 and CC = 0.538, flooring p = 0.002 and CC = 0.323. Thus, the hypothesis stating 'The relationship between ventilation, lighting, humidity, and flooring is associated with ARI in toddlers in the working area of the Cantigi Community Health Center, Indramayu Regency' is accepted, indicating a fairly strong relationship.